Amyloid duration is associated with preclinical cognitive decline and tau PET. Issue 1 (13th February 2020) - Koscik, Rebecca L.; Betthauser, Tobey J.; Jonaitis, Erin M.; Allison, Samantha L.; Clark, Lindsay R.; Hermann, Bruce P.; Cody, Karly A.; Engle, Jonathan W.; Barnhart, Todd E.; Stone, Charles K.; Chin, Nathaniel A.; Carlsson, Cynthia M.; et al.
Abstract: Introduction: This study applies a novel algorithm to longitudinal amyloid positron emission tomography (PET) imaging to identify age‐heterogeneous amyloid trajectory groups, estimate the age and duration (chronicity) of amyloid positivity, and investigate chronicity in relation to cognitive decline and tau burden. Methods: Cognitively unimpaired participants ( n = 257) underwent one to four amyloid PET scans (Pittsburgh Compound B, PiB). Group‐based trajectory modeling was applied to participants with longitudinal scans ( n = 171) to identify and model amyloid trajectory groups, which were combined with Bayes theorem to estimate age and chronicity of amyloid positivity. Relationships between chronicity, cognition, clinical progression, and tau PET (MK‐6240) were investigated using regression models. Results: Chronicity explained more heterogeneity in amyloid burden than age and binary amyloid status. Chronicity was associated with faster cognitive decline, increased risk of abnormal cognition, and higher entorhinal tau. Discussion: Amyloid chronicity provides unique information about cognitive decline and neurofibrillary tangle development and may be useful to investigate preclinical Alzheimer's disease.